(untitled) (Revista de Estudios Teóricos y Epistemológicos en Política Educativa, 2025)
This article investigates the education policies implemented in the early years of Republican Brazil, with an emphasis on the education reform carried out in Paraná by Cesar Prieto Martinez between 1920 and 1924. The analysis is based on a set of official and unofficial historical sources, such as reports from the General Inspectorate of Education, the journal O Ensino (The teaching), and records from the press. Grounded in the contributions of Thomas Popkewitz—especially the concept of “ecologies of reform”—and in the reflections of Carlos Roberto Jamil Cury on the contradictory nature of education policies, the study seeks to understand the reform as a historical and political process marked by power disputes, modernization projects, and attempts to rationalize public education. The research shows that, while aiming to align Paraná’s schools with the Republican ideals of progress, civic education, hygienism, literacy, and the rationalization of teachers’ work, Martinez’s reform reproduced tensions between inclusion and exclusion, innovation and resistance. Analysis of the sources reveals that the reform went beyond the normative sphere, constituting a formative experience shaped by social, cultural, and economic conditions. The study reaffirms the importance of historiographical critique and the use of diverse sources to understand the historical meaning of educational reforms and their repercussions for the development of public schooling in Brazil. Keywords: Education reforms. Cesar Prieto Martinez. Education policies. History of Education. Paraná.